TAMAN WISATA BAHARI DI TANJUNG BENOA, KUTA SELATAN, BADUNG - I Ketut Nuryasa; Putu Gde Ery Suardana (Universitas Dwijendra, 2017)
Bali Island as one of the tourism destinations in Indonesia, is well known in the archipelago as well as abroad. The beauty of nature and the charm of Balinese culture blend with its friendly society. The uniqueness of Balinese culture makes Bali as a tourist destination that always attracts tourists.Badung as a marine tourism destination, where most of it is managed by small entrepreneurs who only engaged in scouting and diving equipment rental. In addition, facilities and infrastructure of marine tourism services provided inadequate such as inadequate dive facilities. Various tourism participation and assistance programs have been developed in Badung regency, by Lembanga International, central government, local government, scientific institutions, non-governmental organizations, private and private sectors to support the development of tourism sector in this area.The research method used is data collection method which includes primary data with interview and observation technique, secondary data that is by literature study and literature supporting book. Data analysis methods that include data grouping, analysis and synthesis and the last is the method of conclusion.So to further develop the existing potential of Tanjung Benoa area, there needs to be a place of service with facilities to further improve services to marine tourism activities for tourists. Besides, with the Tanjung Benoa Marine Park, South Kuta, Badung is expected to be a contribution to further improve the quality of Tanjung Benoa tourism area and can serve as the utilization of human resources, improve the economic structure of the surrounding community and foreign exchange.Keywords: Parks, Tours, Nautical